Preoperative imaging of spinopelvic pathologies: state of the art = Präoperative Diagnostik von spinopelvinen Pathologien : state of the Art - Al Mansour, Haidara; Innmann, Moritz Maximilian; Akbar, M.; Springer, F.; Rehnitz, Christoph (Der Orthopäde, 2020)
The field of musculoskeletal diagnostics and personalized medicine has undergone a revolutionary transformation due to a deeper understanding of skeletal biomechanics and due to technological advancements. Analogous to this transformation, our understanding of spinopelvic conditions has experienced a paradigm shift in terms of both static and dynamic changes in spinopelvic pathologies and enabled a more accurate delineation of the drivers of disability. The purpose of this review is to describe the standard and state of the art of preoperative diagnostic and planning methods for common spinopelvic pathologies and to discuss both the added clinical value and limitations. The rationale is to accelerate the accurate and timely diagnosis and as well as the efficient and safe preoperative workflow.
Gesehen am 25.09.2025